Korean War : biographies - Benson, Sonia; Raffaelle, Gerda-Ann (Detroit : U. X. L., 2002)
Presents biographies of twenty-six men and women who participated in or were affected by the Korean War, including politicians, military leaders, journalists, and nurses
Includes bibliographical references and index
Keywords: Korean War, 1950-1953 -- Biography -- Juvenile literature; Korean War, 1950-1953 -- Biography; Korea (South) -- Biography -- Juvenile literature; United States -- Biography -- Juvenile literature